The Applicable Law for Documentary Credit Disputes - Abraheem Tahe, Researcher. Banin; Abdul-baqi Yousif, Prof. Dr. E’tidal (Basra studies journal, 2024)
Documentary credit is one of the most important and widespread banking operations, and this process is characterized by the multiplicity of parties who belong to different countries. This difference in the country of the contracting parties leads to a conflict between the laws that are intended to be applied to the disputes arising from the application of the documentary credit contract. To determine the applicable law, it becomes Usually to the application of the competent legislation in force or the application of what was agreed upon by the will of the two parties, which is known as the law of will or what the arbitral tribunal decides in the event that the parties agree to resolve the dispute through arbitration.